Geological and energy potential analysis of Küplüce-Gökçesu basin rich in coal and other potential energy resources - Şentürk, Murat (Frontiers in Earth Science, 2023)
The Küplüce-Gökçesu Basin, located in northwestern Anatolia, is an Eocene-aged shallow marine basin known for its rich carbonaceous sediments. The basin is underlined by Paleozoic metamorphic rocks, granites from the Sakarya Massif, and Jurassic-Upper Cretaceous turbiditic and carbonate rocks. The sedimentary deposits in the basin consist of two main lithological units, namely the Tokmaklar and Sazlar Formations. The Tokmaklar Formation comprises marl, bituminous marl, clayey bituminous limestone, Nummulite limestone, and marl-clay-sandstone successions. Economic coal formations are found at the base of the Tokmaklar Formation, along with bituminous limestone and marl. The Sazlar Formation is composed of thick layered sandy limestones and marls, deposited in reefal conditions. Previous studies conducted in the 1980s estimated the coal reserves in the Küplüce-Gökçesu Basin to be around 40 million tons. However, this study reveals the discovery of a new coal seam that was not previously identified, with a potential thickness of approximately 11 meters. This discovery suggests that the coal reserves in the region could be significantly larger than previously known, potentially 5-6 times greater. The quality of the Küplüce-Gökçesu coals is classified as semi-bituminous hard coal of the lower bituminous coal group, based on chemical analysis results. This study contributes to the understanding of the geology and coal potential of Eocene basins in Anatolia and provides valuable information for future exploration and exploitation activities.